2015
DOI: 10.1007/s11356-015-5328-3
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and molecular effects of sediment-bound metals in zebrafish embryos

Abstract: Predicting the bioavailability and effects of metals in sediments is of major concern in context with sediment risk assessment. This study aimed to investigate the bioavailability and molecular effects of metals spiked into riverine sediments to zebrafish (Danio rerio) embryos. Embryos were exposed to a natural and an artificial sediment spiked with cadmium (Cd), copper (Cu), nickel (Ni) and zinc (Zn) individually or as a mixture at concentrations ranging from 150 to 3000 mg/kg dry weight (dw) over 48 h, and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 73 publications
3
8
1
Order By: Relevance
“…In the present study, to better analyze the behavioral changes, the treatment doses were chosen based on the malformation rate reached at approximately 40% at 120 hpf to optimize the analysis of behavioral changes. Moreover, consistent with previous studies [24,35], we found that all 3 metals accumulated in the zebrafish tissue.…”
Section: Effects Of Metals On Neurexin 2a Expression In Zebrafishsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, to better analyze the behavioral changes, the treatment doses were chosen based on the malformation rate reached at approximately 40% at 120 hpf to optimize the analysis of behavioral changes. Moreover, consistent with previous studies [24,35], we found that all 3 metals accumulated in the zebrafish tissue.…”
Section: Effects Of Metals On Neurexin 2a Expression In Zebrafishsupporting
confidence: 93%
“…Moreover, consistent with previous studies[24,35], we found that all 3 metals accumulated in the zebrafish tissue. The most predominant malformations caused by treatment with Cd, Mn, and Pb were yolk sac edema, pericardial edema, and curly spinal cord, respectively.…”
supporting
confidence: 93%
“…The LC 50 values for the static- and semi-static exposure were comparable to previously published values determined using zebrafish embryos, which were 30.1 mg L -1 [36] and 14.1 mg L -1 [37], respectively.…”
Section: Resultssupporting
confidence: 85%
“…This could be explained by assuming that permeation of chemicals is reduced by the chorion as for organic pollutants and lipophilic drugs [ 31 , 32 , 33 ]. For that reason, it is necessary to take into account two parameters: bioaccumulation and chorion permeability [ 33 ].…”
Section: Resultsmentioning
confidence: 99%